Evaluasi sistem otomasi IBRA V6 di Perpustakaan SDIT Luqman Al-Hakim Internasional Yogyakarta - Nurul Alifah Rahmawati (Universitas Padjadjaran, 2018)
Implementation of automation systems in the library make it easy access for students and can improve the quality of its services. SDIT Luqman Al-Hakim International Yogyakarta’s Library has implemented an IBRA V6 automation system in a library services. However, this library still often do the service manually although it is automated. Therefore, evaluation of IBRA V6 automation system in library is needed. This study aims to evaluate the performance of IBRA V6 based library automation system on the circulation section of SDIT Library Luqman Al-Hakim Internasional Yogyakarta. The method of research is a qualitative approach that focuses on the process of circulation, borrowing and return collection. Data collection techniques use observation, interview and documentation. This research is based on service performance theory then formulated with theory of success model of DeLone & McLean system which got 5 indicator from 3 Aspect that is supporting facilities, system quality, operational, service and resultant impact. Of the five indicators are obtained the result that the first indicator of supporting facilities was adequate, but the space was very tightso that the overall service is less. As for other indicators obtained good results, effective and efficient. So the conclusion researchers that the performance of IBRA V6 based library automation system on the circulation process in the library of SDIT Luqman Al Hakim International is good.